The New Cults : A Threat to Unity and Authentic Humanity - Debold, Walter (Journal of Dharma, 1987)
A decision was made in the Vatican in 1984 to survey the bishops of the world to discover how serious is the problem of "cults," or if, indeed, there is a problem. This investigation brought into collaboration four of the Vatican offices: the Pontifical Council for Culture, and three secretariats, the one for Promoting Christian Unity, the one for Non-Christians and the one for Non-Believers. By October of 1985 there were about seventy-five replies received from episcopal conferences around the world. The results of the survey were published May 3, 1986 in what was described as a "progress report." It appeared in Origins for May 22, 1986.A body of literature has been building up around the world relevant to the problems presented by the cults and by manipulation in general. Some of it has come from the victims themselves,s some psychologists, counsellors and clergy who wrestle with the problem of coping with cults.